Kampf um Würde in der Arbeit Rechtspopulismus als Ausdruck eines moralischen Unrechtsempfindens - Schwuchow, Torben (Schriften der Themengruppe Populismus in der DVPW, 2023)
This book argues that right-wing populism expresses the moral sense of injustice of the working classes. The struggle for dignity at work is fundamental in this respect. In the first part, approaches to populism research are critically discussed and the research thesis is theoretically developed. In the second part, a concept for empirical investigation into the struggle for dignity at work is presented and the research thesis is empirically tested. This study adds a new perspective to current research on populism and contributes to the currently reemerging research debates on the relationship between work and democracy. The author conducts research in the areas of democratic theory and political economy at the WSI.